PERSEPSI KEADILAN PAJAK TERHADAP PERILAKU KEPATUHAN WAJIB PAJAK - Rosmawati Rosmawati (Jurnal Riset Perpajakan: Amnesty, 2021)
This study has a perception that tax justice affects personal taxpayers at KPP Pratama Makassar Utara. The statistical method used to test the hypothesis is multiple regression. The results showed that the perception of tax justice has a positive and significant effect on taxpayer comments. The better tax justice, the more taxpayers will be in paying taxes. the level of individual taxpayers on the dimension of perceived tax justice by self-interest.